A caminho com Jesus ressuscitado: uma leitura hermenêutico-eclesial de Lc 24,13-35. - Cunha, Antônio Diego Santos da (2014)
The main theme of this work is the experience that Cleopas and the other disciple had with the risen Jesus on the road to Emmaus. It is a study of the importance and influence of the experience of Jesus' resurrection in the early Church and today. Innature, it is a hermeneutic-ecclesial reading of Lk 24:13-35. The aim is to present a study of the pericope of the disciples of Emmaus from the point of view of biblical hermeneutics and within the framework of ecclesial hermeneutics. As for the methodology, bibliographical research is used in the search for the message presented in the above-mentioned Lucan text, based on consultation of printed and digital works by various authors who have worked on the subject. As a result, this work has produced a pertinent reflection on the experience of the Risen Lord, which can be applied to ecclesial life. The final considerations summarize the whole work, including the perceptions and conclusions reached during the construction of the work.